Secretors of HBGA and Susceptibility to Norovirus and Rotavirus Diarrhea. Issue 9 (September 2021) - Faden, Howard; Schaefer, Beverly A.
Abstract : Histo-blood group antigen contains oligosaccharides that serve as receptors for norovirus (NoV) and rotavirus (RV). The receptors are only present on the surface of intestinal mucosal epithelial cells of secretors; therefore, secretors are susceptible to NoV and RV diarrhea and nonsecretors are resistant. The prevalence of secretors in different countries varies between 50% and 90%. Secretor rates evolved in response to environmental pressures such as infectious diseases.